Teacher trainees’ creativity and cognitive engagement in using mobile technology for video project: a case study - Syed Hassan, Sharifah Sariah; Mohin, Mohaida (2015)
This research investigates the use of mobile technology namely the smart hand phone in developing instructional video project for language learning. The purpose of this study is to analyse students’ creativity and cognitive engagement when developing instructional video through the use of smart hand phone. Firstly, the research attempts to address the relationship between students’ creativity based on ICEDIP (inspiration, clarification, evaluation distillation, incubation and perspiration) and cognitive engagement in mobile learning environment.. Secondly, the research further examines each creativity process in contributing the effect on cognitive engagement. The study employed a mix method of quantitative and qualitative research. A survey using adapted questionnaire was carried out on a focus group of 52 first semester teacher trainees (Bachelor Degree in Education) specializing in English language. Semi structured interviews were carried out on three students in order to gain an in depth understanding of the students’ creativity and cognitive engagement. A correlation analysis was used to identify the relationship between creativity and cognitive engagement. Further analysis of Hierarchical Multiple regression was employed to identify the specific items for creativity process affecting cognitive engagement. The results from the correlation analysis indicate a significant relationship between creativity and cognitive engagement, which is also supported by the interviews. Student’s creativity has contributed to a meaningful learning when smart hand phone is used for learning. Further findings from the interviews show some indicators for the researchers to improve the instructional strategies in future. Implications and discussions are elaborated based on the contribution to the development and design of the curriculum.